Pressupostos condicionantes da interpretação do direito tributário - Pasinato, Rosana Oleinik (2011)
The present study intends to establish parameters of law taxes interpretation, denominated conditional presuppositions. Understanding the law as a language phenomenon and exegesis activity as a meaning construction done by the interpreter, does not implicate empowering the individual with an absolute subjectivity, which dispenses the observance of the meaning expectations present at the historical and cultural context where it is done. After defining the philosophical premises that will support our dogmatic investigations, the conditional presuppositions of law taxes interpretation are defined, as well as the concept of law interpretation as a prescriptive language system, his relevance and the study of the clauses about the subject that are in the legal system and about the methods of exegesis traditionally conceived by doctrine that support the arguments used in the Court begins